(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The current research seeks to evaluate keywords related to e-banking (also known as electronic banking) concerns from 1991 to 2021, with the first publication on this topic appearing in the Scopus database. Using the Scopus database, this work investigated and assessed 2954 research papers. To achieve the results, bibliometric analysis and content analysis were performed using Excel and Biblioshiny R Studio software. Furthermore, the findings of this article show that worldwide trends and expanded production led to numerous changes, and the most trending topic was linked with e-banking. This study discusses how the effect of the internet on customers' perceptions and satisfaction in the banking industry has evolved in the last three decades. The number of publications increased significantly from 2012–2021, and the 10 journals, authors, affiliations, and countries are identified. Customer satisfaction, perception, online banking, e-banking, humans (especially middle-aged adults), the service quality industry, and banks are among the well-known studies found in the existing literature. Following up on the points in the preceding literature, numerous major study gaps are identified, as well as recommendations for further research. The bibliographic data employed in this search of the Scopus database, as well as the methodology itself, have some limitations; therefore, combining multiple methodologies will be necessary to uncover the sector beyond modern-day discovery. This study will aid capable researchers, scientific journal editors, and bankers in comprehending current research progress and evolution in customer satisfaction through the usage of the internet in the banking sector. In comparison to the current bibliometric literature, this bibliometrics investigates masking co-authorship, quotation, bibliographic coupling, co-authorship, and co-quotation for customer perceptions and satisfaction with e-banking.